2016
DOI: 10.1159/000453262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Exome Sequencing Reveals <b><i>MKRN3</i></b> Pathogenic Variants in Familial and Nonfamilial Idiopathic Central Precocious Puberty

Abstract: Background/Aims: Idiopathic central precocious puberty (ICPP) is the premature activation of the hypothalamic-pituitary-gonadal axis in the absence of organic disease. Up to now, just gain-of-function mutations of KISS1/KISS1R and loss-of-function mutations of the maternally imprinted gene MKRN3 are the known genetic causes of ICPP. Our intention is to evaluate variants present in genes related to the pubertal onset pathway that could act as disease-causing or predisposing variants. Methods: We studied the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…In 6 out of 19 (31.5%) patients (3/13 CPP patients and 3/6 EP patients) we found the synonymous variant c.663C > T (rs2239669). According to ExAC, the allele frequency of this polymorphism is 0.2815 [16]. Another synonymous variant (rs140467331) was found in one of our CPP patients, as well as one missense variant (rs760981395) in another CPP patient.…”
Section: Gpr54 and Mkrn3 Genes Analysismentioning
confidence: 59%
See 1 more Smart Citation
“…In 6 out of 19 (31.5%) patients (3/13 CPP patients and 3/6 EP patients) we found the synonymous variant c.663C > T (rs2239669). According to ExAC, the allele frequency of this polymorphism is 0.2815 [16]. Another synonymous variant (rs140467331) was found in one of our CPP patients, as well as one missense variant (rs760981395) in another CPP patient.…”
Section: Gpr54 and Mkrn3 Genes Analysismentioning
confidence: 59%
“…Our paper confirms the presence (and expands the phenotype) of mutations and polymorphisms of KISS1R and MKRN3 genes, not only in ICPP patients but also in early puberty subjects. However, our study has some limitations: we were not able to perform functional studies to demonstrate the pathogenicity of the variants we found; in addition, it was not possible to obtain DNA samples from the fathers of patients with mutations in order to verify paternal inheritance, which had been demonstrated in previous reports [16]; finally, our sample scale was quite small.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, Bessa and cols.. (16) reported MKRN3 mutations in 8 out of 20 boys with apparently idiopathic CPP, reporting a high frequency of MKRN3 mutations in male with CPP previously classified as idiopathic. Further studies performed in centers from different countries, as well as a recent systematic review, confirmed that defects in MKRN3 are the most common cause of genetic CPP, with prevalence ranging from 33 to 46% in familial cases (15,17), and 0.4 to 5% in sporadic cases (16,(18)(19)(20).…”
Section: Inactivating Mutations In Imprinted Gene Mkrn3 Leading To Famentioning
confidence: 76%
“…18 Subsequently, mutations in MKRN3 have been described in many additional patients with CPP throughout the world. [21][22][23][24][25][26][27][28][29][30][31][32] For a recent systematic review and meta-analysis of the MKRN3 mutations identified in patients with CPP to date, see the study by Valadares et al 33 Precocious puberty is clinically defined by the development of secondary sexual characteristics before the age of 8 years in girls and 9 years in boys, which corresponds to 2.5 to 3 standard deviations below the mean age of puberty onset, as defined by population studies. 34 Early age of puberty has been associated with many deleterious health effects such as cancer, cardiovascular disease, and metabolic and behavioral disorders.…”
Section: Mkrn3 Mutations In Central Precocious Pubertymentioning
confidence: 99%